The Implementation of Tactical Command Posts (Poskotis) and Rest Areas as A Form Of Public Service For Eid Al-Fitr Homecomers in West Java Region IV - Azhahra Dwisrireno, Sefani; Azzahra, Pingka; Siswoyo, Mukarto; Wulandari, Sri (ann4publisher@gmail.com, 2024)
Eid is synonymous with the tradition of returning home (mudik), and its implementation requires the implementation of Eid transportation that is safe, secure, and comfortable for homecomers. This research uses qualitative methods and aims to know the quality of service regarding the implementation of Poskotis and Rest Area. The results of this study conclude that the Implementation of Poskotis and Rest Area by The West Java Provincial Transportation Office UPTD PPPLLAJ Region IV is considered not optimal because in its implementation, there are still several problems, such as the lack of service services in the form of facilities and infrastructure and less optimal socialization activities. For this reason, improvements need to be made to improve the quality of public services per the dimensions of tangibles and responsiveness.